Anterograde fixation of inverted oblique medial malleolus fractures: case report - Chami , Sávio; Lima, Thiago; Pallottino, Alexandre; Scorza, Breno; Franco , José; Bitar, Rogério (Journal of the Foot & Ankle, 2021)
Fractures of the medial malleolus are common, with avulsion being the main trauma mechanism. In simple transverse fractures, retrograde fixation with interfragmentary screws is the most common means of achieving anatomical reduction and absolute stability. However, greater attention must be paid in cases of inverted oblique fractures, which make traditional fixation difficult. We report a case in which anatomical reduction and stabilization were achieved using a reduction clamp and two headless compression screws placed anteriorly, resulting in a mechanically stable, safe and effective repair. Level of Evidence V, Therapeutic Studies; Expert Opinion.